Distorsiones cognitivas en estudiantes Latinoamericanos que presentan estrés - Córdova Calderón, Mariuxi Marisela (2024)
Stress is a natural reaction that human beings have when exposed to difficult situations in their daily lives, especially students, since by experiencing different changes within their educational unit they generate clinically significant discomfort in academic performance or behavior. Furthermore, when experiencing a stressful event, in many cases, students misinterpret the situation, causing errors in thinking called cognitive distortions. The general objective of the current work was to describe the scientific evidence of the main cognitive distortions in Latin American students with the presence of stress. To achieve the objective of the research, a bibliographic review was carried out with a quantitative approach and a non-experimental design, which had 74 scientific articles, which through a tool called PRISMA, 58 articles were excluded taking into account the inclusion and exclusion criteria. Finally, through non-probabilistic sampling, a sample of 16 scientific articles published until 2023 was obtained, resulting in the main cognitive distortions in Latin American students being the fallacy of divine reward, you should and filtering with a presence of medium stress in the students